PENGARUH FASILITAS DAN KUALITAS LAYANAN TERHADAP KEPUASAN PENUMPANG DI PELABUHAN INDONESIA REGIONAL 2 TANJUNG PRIOK - Febillah Irnawaty (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The development of technology and knowledge at this time is increasingly advanced. Therefore, many parties encourage companies to develop faster and compete in a more competitive market. The study was conducted at the Port of Tanjung Priok in North Jakarta which is located at Jalan Pelabuhan Raya no 9 Tanjung Priok. Ports are managed by Business Entities (BP) to determine the quality of facilities and services for passenger satisfaction. The population of this study is passengers traveling to Tanjung Priok port by the Kelud ship in 2022 totaling 343,559 passengers. A sample of 385 people was taken using non-probability sampling technique and random sampling method. Data collection was carried out through a questionnaire using an interval scale (Likert scale) which measures 21 statement indicators using primary and secondary data. The analysis used was multiple linear regression and processed using SPSS 26. Meanwhile, the results of the F test had a significant effect indicating that the quality of facilities and services had a significant effect on customer satisfaction at Tanjung Priok Port, North Jakarta. The results of several T-tests show that facilities have a significant effect on passenger satisfaction at Tanjung Priok North Jakarta Port, and service quality has a significant effect on passenger satisfaction at North Tanjung Priok Port, Jakarta.